Etymological Parallels in Baltic and Indoiranian in Names of Animals and Beasts - Chomičenkienė, Aleta; Maksvytytė, Virginija (Acta Orientalia Vilnensia, 2002)
In this paper words which in Tocharian name animals and beasts are analyzed. There are 9 words, which have etymological parallels in Baltic, Indoiranian and other Indo-European languages. There are 5 words from 9 name domestic animals: lie. avís, la. avs ir skr. áviḥ ‘sheep’; lie. ašv à ir skr. áśvā ‘mare’; lie. ožys, la. āzis, ir skr. ajàḥ ‘goat’; lie. ė́ras, la.jērs, pr. eristian ir skr. úraṇa ‘lamb’; lie. kárvė, pr. curwis ir skr. śṛ́ṅga ‘cow’; 4 of them name beasts: lie. vilkas, la. vílks ir skr. vṛ́kaḥ ‘wolf’, lie. ū́dra, la. ūdrs, pr. udro ir skr. udráḥ ‘otter’, lie. šẽškas, la. sesks ir skr. jáhakā ‘polecat’; lie. bẽbras, bèbras, la.bebrs, pr. bebrus ir skr. babhrúḥ ‘beaver’. Those names of animals and beasts have retained many of the most archaic feature of the Indo-European vocabulary, cf. ėras, ožys, ašva, vilkas, bebras, ūdra. The remaining 2 words, cf. avis, karvė, šeškas which name animals and beasts, frequently are derivatives from Indo-European verbal or substantivel roots.